Agama dan Pengalaman Keberagamaan - Manshur, Marsikhan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
Religion is the reality of the necessities of life and life for everyone because of the belief in the unseen substance that emerges as a force beyond the physical world and ratio. Religious belief thus becomes a necessity. As a logical consequence, that belief must be reflected in all real behavior as fact. Thus, it can be proved that the difference between religious and non-religious conditions. To search for it, what is religion really? And what and how is the process of religiousness? Answers to such questions are expected to be obtained through the focus of discussion in this paper.